2023
DOI: 10.3390/ijms241411582
|View full text |Cite
|
Sign up to set email alerts
|

Pim Kinases: Important Regulators of Cardiovascular Disease

Abstract: Pim Kinases; Pim-1, Pim-2, and Pim-3, are a family of constitutively active serine/threonine kinases, widely associated with cell survival, proliferation, and migration. Historically considered to be functionally redundant, independent roles for the individual isoforms have been described. Whilst most established for their role in cancer progression, there is increasing evidence for wider pathological roles of Pim kinases within the context of cardiovascular disease, including inflammation, thrombosis, and car… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 148 publications
0
3
0
Order By: Relevance
“…The PIM kinase family plays a crucial role in the inflammatory process. Studies have shown that the three PIM family kinases also fulfil broader pathological functions in cardiovascular diseases, including in inflammation, thrombosis and cardiac injury ( Nock et al, 2023 ). In a transcriptomic study of inflammation in psoriasis, PIM3 kinase is located among key regulator transcripts ( Garshick et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…The PIM kinase family plays a crucial role in the inflammatory process. Studies have shown that the three PIM family kinases also fulfil broader pathological functions in cardiovascular diseases, including in inflammation, thrombosis and cardiac injury ( Nock et al, 2023 ). In a transcriptomic study of inflammation in psoriasis, PIM3 kinase is located among key regulator transcripts ( Garshick et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Dr Alexander Brill (University of Birmingham, UK) kicked off this session by presenting new data on how hyperactivation of inflammasomes (NLRP3) in megakaryocyte linage induces anaemia and inflammation in mouse models. Dr Sophie Nock (Manchester Metropolitan University, UK) discussed how PIM kinases are novel regulators of platelet and megakaryocyte thromboxane A2 receptor (TPαR) and CXCR4 ( 20 ). New in vivo studies on Protein S and the TFPIα pathway were discussed by Dr Anastasis Petri (Imperial College London, UK) who described the role of Protein S in acting as a co-factor for human TFPIα and in controlling fibrin accumulation.…”
Section: Oral Communication Sessionsmentioning
confidence: 99%
“…PIM1 is mainly expressed in B lymphocyte and myeloid system, and overexpressed in hematopoietic malignancies and prostate cancer (from GENECARD). The PIM1 gene has been reported to not only exhibit widespread expression in various cardiovascular tissues, such as the heart, coronary artery, aorta, and blood, but also show high expression in cardiovascular diseases affected by numerous risk factors (Nock et al, 2023). Noteworthily, PIM1 has been underscored to promote inflammation (Yang & Chen, 2023).…”
Section: Introductionmentioning
confidence: 99%